Implications of presenting to hospital with AF: the REVIEW AF study. (25th November 2020) - Gallagher, C; Wong, C.X; Hendriks, J.M; Bednarz, J; Elliott, A.D; Linz, D; Middeldorp, M.E; Mahajan, R; Lau, D.H; Sanders, P
Abstract: Background: There is a growing burden of hospitalizations due to atrial fibrillation (AF). The implications of hospitalisation to the individual with AF has not been well characterized. Purpose: To characterise the consequences of presenting to hospital with AF. Methods: Individuals presenting to the emergency department (ED) of three hospitals in South Australia from March 2013 to February 2014 with a primary diagnosis of AF were enrolled. Based on coding and individual electronic medical record review all re-presentations over follow up were characterised as: 1) AF related; 2) cardiovascular related (excluding AF); or 3) all other causes. Mortality over follow up was also determined. Results: The study cohort comprised of 437 individuals with an AF related index presentation. Mean age was 69±15 years and 49.9% were male. Individuals were followed for a mean of 3.7±0.4 years. There were 2304 unplanned presentations over follow up. The percentage of the study cohort who presented to the ED or were admitted to hospital over follow up is detailed in Figure 1. Compared to individuals who did not have a hospital admission for AF over follow up, those who were readmitted for AF were more likely to be hypertensive (63.2% vs 49.3%, p<0.001); and have a higher CHA2DS2-VASc score (3.2±1.8 vs 2.7±1.9, p=0.002) and HAS-BLED score (2.0±1.0 vs 1.5±1.1, p<0.001). A total of 71 individuals (16.2%) died during the follow-up period (annual mortality rate of 3.78%). Conclusions: A hospital presentation with a primary diagnosis of AF identifies individuals at high risk of repeat hospitalisations and death. Urgent studies are needed to improve management of this high-risk cohort. Funding Acknowledgement: Type of funding source: None